POTENSI SUSU KERBAU "DADIH" SEBAGAI AGROWISATA KULINER KABUPATEN SOLOK, SUMATERA BARAT - Anton Gunarto (JURNAL KEPARIWISATAAN, 2010)
Dadih buffalo milk is well known for its delicious and health benefit and can be one of superior alternative commodity for ranch agriculture tourism in Solak Regency. The objective of this study is to identify the potential of and conservation efforts or rebuilt image for dadih buffalo milkfo1#development of agrotourism in Solak District. The study find out that a tour to the village of dadih buffalo milk (Dewi Abadi), Alahan Panjang or Air Dingin village in Subdistrict of Lembah Gumanti has a good development prospect as a center of agrotourism area for buffalo milk ranch. To Support Dewi Abadi development, it needs a structured technical sector to organize the area, human resources development program, marketing models in order to sell agrotourism product, and to prepare methods for funding and mechanism for its m.anagement.